A comparative study of the outcomes of ribbon gauze and merocele methods of nasal packing after septal surgery - Ray, Ritam; Ashim Sarkar; Mondal, Tarun Kumar; Sannigrahi, Rajarshi (Asian Journal of Medical Sciences, 2024)
Background: Septal surgery is one of the most commonly performed procedures in Otolaryngology. Following septal surgery, nasal packing is administered to prevent potential postoperative complications, including septal hematoma, hemorrhage, and synechiae formation. Nasal packing is commonly done using either ribbon gauze or non-absorbable materials like Merocele (Medtronic Xomed Inc., Jacksonville, FL, USA). Aims and Objectives: The objective of the study is to compare the post-operative outcomes of ribbon gauze packing and merocele packing. Materials and Methods: The study was a prospective observation study, conducted in Burdwan Medical College and Hospital from August 2023 to October 2023. The study population was 40 with equal distribution between the two groups. Patients older than 18 years undergoing only septal surgery are included in the study. All the surgeries are performed by the same surgeon, both packs are removed after 48 h and followed up with diagnostic nasal endoscopy (DNE) after 1 month. Statistical analysis was done using SPSS version 22.0 (IBM Inc., US). Results: The total number of patients in our cohort was 40, out of which 20 were given ribbon gauze packs (Group A) and the rest were given merocele packs (Group B). The mean visual analog scale score for nasal pain (4.25±1.77), headache (4.30±1.63), dysphagia (2.50±1.15), sleep disturbance (3.15±1.09) in Group B was significantly lower than in Group A (6.65±1.63, 5.40±1.70, 4.00±1.84, and 5.40±2.35 respectively, p all<0.05). The mean of the postnasal drip score was lower in Group B, though that did not reach statistical significance (2.75±1.070 vs. 3.25±1.650, p=0.264). There were no significant differences between the two groups with respect to the age of the patients, gender distribution, or the presence of synechiae, granulation tissue, or signs of infection on DNE. Conclusion: Although both the merocele and ribbon gauze packs can be suggested for use after septal operations, the merocele pack has the benefit of producing much less morbidity. Merocele cost is a major constraint at present so we should try to develop a similar nasal pack with less cost to benefit the maximum population.